Overexpression of miR-4433 by suberoylanilide hydroxamic acid suppresses growth of CML cells and induces apoptosis through targeting Bcr-Abl - Wu, Haiyan; Yin, Jingyi; Ai, Zhengdong; Li, Guiming; Li, Yan; Chen, Li (Journal of Cancer, 2019)
: Targeting Bcr-Abl is the key for the treatment of CML. Although great progress has been achieved for the treatment of CML patients in chronic stage, effective drugs with good safety are not available for those in advanced stages of CML patients. In present study, a histone deacetylase inhibitor, suberoylanilide hydroxamic acid (SAHA), was used to screen for microRNA that can target Bcr-Abl. : RT-qPCR was used to determine Bcr-Abl and miR-4433 transcription level in CML cells. In CML cells, Proteins including PARP, caspase-3, acetyl-histone 3, histone 3 and Bcr-Abl, as well as Bcr-Abl downstream proteins were detected using western blot. Cell viability and apoptosis were monitored respectively by MTS assay and flow cytometry. The correlation between miR-4433 and Bcr-Abl was determined by luciferase reporter assay. The anti-tumor effect of miR-4433 to K562 cells was evaluated by nude mouse xenograft model in vivo. : SAHA up-regulated the acetylation level of histone 3, and effectively inhibited Bcr-Abl mRNA level and its downstream signal transduction pathway, while inhibiting the growth of CML cells and inducing apoptosis. Furthermore, bioinformatics tools predicted that miR-4433 is a putative microRNA targeting Bcr-Abl and that the expression level of miR-4433 was significantly increased after SAHA treatment in K562 cells. Luciferase activity analysis revealed that miR-4433 directly targets Bcr-Abl. Additionally, transient expression of miR-4433 abrogated Bcr-Abl activity and its downstream signaling pathways while inducing apoptosis in K562 cells. Moreover, stable expression of miR-4433 suppressed Bcr-Abl and its downstream signaling pathway, and inhibited the growth of K562 cells in vitro and the growth of K562-xenografts in nude mice. : miR-4433 was identified as a microRNA targeting Bcr-Abl, which may be subject to epigenetic regulation of SAHA, a histone deacetylase inhibitor that has been approved by the US FDA for the treatment of cutaneous T-cell lymphoma. The findings of this study provide a molecular basis from another angle for the use of SAHA in the treatment of CML.